ENSURING THE RIGHT TO EDUCATION IN THE CASE LAW OF THE ECTHR: STANDARDS OF EQUALITY AND CONTEMPORARY CHALLENGES - Renov, Ievgen (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. The article analyses international legal standards for ensuring the right to education, based on the case law of the European Court of Human Rights. It explores how the Court develops the concept of equal access to education, the prohibition of discrimination and the balance between the right to education and freedom of belief. Summary of the main research findings. Central to the analysis is the ECtHR’s case law concerning discrimination against Roma children, including D.H. and Others v. the Czech Republic, Horvath and Kiss v. Hungary, Orsus and Others v. Croatia, and Sampanis and Others v. Greece. These landmark judgments have helped shape the Court’s approach to prohibiting indirect discrimination as well as promoting inclusive education. Other categories of cases were also examined, which reveal the multidimensionality and diversity of educational rights, allowing for a comprehensive analysis of the Court’s approaches to ensuring a balance between the interests of society, the state, and the individual. In addition, the article also examines judgments defining the limits of state interference in the exercise of freedom of belief in education (Lautsi v. Italy, Papageorgiou and Others v. Greece, Leyla Sahin v. Turkey). Other categories of cases were also reviewed which reveal the multidimensionality and diversity of educational rights, allowing for a comprehensive analysis of how the Court seeks to balance the interests of society, the state, and the individual. The study demonstrates that the right to education encompasses not only formal access to educational institutions but also a broad range of social and legal guarantees – equal opportunities, respect for diversity, freedom of belief, inclusiveness, and non-discrimination in the educational process. Special attention is paid to the contemporary challenges posed by the war in Ukraine, which have jeopardized the realization of children’s rights (including educational rights) as children are the most vulnerable group. The author emphasizes that compliance with ECtHR standards should serve as a key benchmark for the Ukrainian state. Conclusion. The article argues that the ECtHR’s case law has been forming a systemic doctrine of educational rights, in which the concept of genuine (rather than merely formal) equality and the positive obligations of states play a central role. The Court consistently stresses that states must not only refrain from violations but also take proactive measures to prevent discrimination and ensure effective access to education.